The prevalence of cyberchondria and the impact of skepticism on medical decisions among Imam Mohammed Ibn Saud Islamic University students, Riyadh, Saudi Arabia - Khalid A. Bin Abdulrahman; Sultan Khalid AL Musfir; Abdullah Suliman Alforaih; Asim Mohammed Alshehri; Ayed Khalid Aldossari; Fahad Dawood Bin Dawood (Journal of Family Medicine and Primary Care)
The internet significantly impacts the occurrence and prevalence of cyberchondria because it provides easy access to a large amount of health data that can describe any medical condition in detail. Cyberchondria develops due to exposure to the vast and easily accessible online health information that causes health worries. Objectives: To assess the prevalence of cyberchondria among Imam Mohammad Ibn Saud Islamic University (IMSIU) students and determine the impact of patient skepticism on medical decisions. Methods: A cross-sectional study was conducted among IMSIU students. A questionnaire was distributed to participants via Google Forms. Data were collected and analyzed by using SPSS. Results: This study involved 798 respondents. Female participants represented 51.1%. Most of the participants were between 21 and 23 years old. More than one-third of students studied in the College of Medicine (36%). Almost 20% of students panicked about their condition when they read online. Excessiveness was the most severely affected construct (63.7%), followed by the reassurance subscale (46.4%). Compulsion was the least affected construct, while distress was moderately affected. Divorced and married students showed significantly higher cyberchondria severity scores than single respondents (P value = 0.020). Conclusion: Our findings suggested that IMSIU students had a relatively high prevalence of cyberchondria. More efforts are required to raise public awareness of appropriate internet usage for health-related information.